Pengembangan PENGEMBANGAN ODENG DARI SURIMI IKAN BULAN-BULAN (MEGALOPS CYPRINOIDES): EVALUASI SENSORI SERTA PERUBAHAN PH DAN KADAR AIR SELAMA PENYIMPANAN BEKU: Indonesia - Abdul Rahman; Siti Hajar (Program Studi Teknologi Hasil Perikanan|Fakultas Pertanian|Universitas PGRI Banyuwangi, 2026)
The Indo-Pacific Tarpon (Megalops cyprinoides Broussonet, 1782) is a common by-catch species that remains underutilized despite its high protein content (25,5g of protein/100g of fish). This study aims to innovate a frozen food product in the form of fish